Ireland : Financial Sector Assessment Program-Detailed Assessment of Observance on the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses findings of the Detailed Assessment of Observance on the Insurance Core Principles on Ireland. It highlights that the Central Bank of Ireland (CBI) has made significant progress in updating the regulatory regime, and the impending implementation of Solvency II (SII) is expected to address most of the regulatory gaps noted in the assessment. The Central Bank Supervision and Enforcement Act of 2013 has significantly enhanced CBI's supervision and enforcement powers. CBI's preparation for SII is well advanced, and a dedicated SII project has been in place since 2010.